Universal Credit: Welfare reform and mental health - Brewer, Mike; Dang, Thang; Tominey, Emma (Elsevier BV, 2025)
The UK Universal Credit (UC) welfare reform simplified the benefits system whilst strongly incentivising a return to sustainable employment. Exploiting a staggered roll-out, we estimate the differential effect of unemployment under UC versus the former system on mental health. Groups with fewer insurance possibilities – single adults and lone parents – experience a mental health deterioration of 8.4-13.9% standard deviations which persists into the subsequent year. For couples, UC partially or fully mitigates mental health consequences of unemployment. Exploring mechanisms, for single adults and lone parents, reduced benefit income and strict job search requirements dominate any positive welfare effects of the reduced administrative burden of claiming benefits.